Sistem Informasi Akuntansi Atas Aset Hak Guna Berbasis Aplikasi - Djumiyati, Dewi; Munandar, Agus (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The aim of this study is to develop an accounting information system as an application using a framework laravel to support the calculation of depreciation  and interest expense on the right-of-use assets of PT Bank Oke Indonesia, Tbk. Methodology/approach: The research methodology used the Laravel Framework with PHP programming language, MySQL as the database, and testing with Black Box Testing. Results/findings: This research shows that the accounting information system based on the Laravel Framework has been successfully developed according to the agreed-upon design, as evidenced by the testing results, and operates according to the requirements. Conclusions: This study develops an accounting information system for right-of-use assets by designing a PSAK 73 application using the Laravel framework with the PHP programming language, MySQL database, and black box testing. The application supports storing lease agreements, calculating Net Present Value (NPV), right-of-use asset values, lease liabilities, depreciation, and interest expenses, as well as generating journal entries for depreciation and accumulated depreciation automatically to reduce errors and improve data accuracy. Limitations: This study is limited to a single case study of PT Bank Oke Indonesia (TBK).  This application is not representative of all companies in the banking industry, and is only designed for Bank Oke Indonesia. Contribution: This research is beneficial for Bank Oke Indonesia in calculating depreciation expense and interest expense rights to use assets and information technology to improve the quality of financial reporting.